Rethinking the mosaic : investigations into local water management : themes from collaborative research - Moench,Marcus(Editor) Caspri,elisabeth(Editor) Dixit,Ajaya(Editor) (Nepal Water Conservation Foundation and the Institute for Social and Environmental Transition, Boulder, Colorado, 1999)
With reference to India and Nepal.